UZBEK PEOPLE'S PHYTOLATRIC VIEWS - Baxtiyor Rejavaliyevich Kholmuratov (Sciental Journals Publishing, 2025)
This article analyzes the phytolatrical (plant world) views of the Uzbeks of the Fergana Valley from a historical, philological, and ethnographic perspective. In the article, the author focuses on the plants that play an important role in the daily life of the Uzbeks of the valley, their types and functions, the place names associated with them, and the religious and secular interpretations of these elements.
Keywords: Fergana Valley, Uzbeks, phytolatry, rituals, customs, traditions, tree, mulberry, pomegranate, willow, jiyda, agriculture, livestock, shamanism, attributes.